Redefinition of the genus Allonychiurus Yoshii, 1995 (Collembola, Onychiuridae) with description of a new species from China - Xin, Sun (Pensoft Publishers, 2011)
Abstract. In this paper, we describe a new species of the genus Allonychiurus Yoshii, 1995, characterized by the presence of an apical swelling on the fourth antennal segment as well as a combination of chaetotaxic and pseudocellar characters. The genus Allonychiurus is redefined. Four of its species are considered as incertae sedis: Allonychiurus michelbacheri (Bagnall, 1948), Allonychiurus spinosus (Bagnall, 1949), Allonychiurus caprariae (Dallai, 1969) and Allonychiurus sensitivus (Handschin, 1928). The three species Allonychiurus borensis (Beruete, Arbea & Jordana, 1994), Allonychiurus sensilatus (Thibaud & Massoud, 1979) and Allonychiurus vandeli (Cassagnau, 1960) are removed from Allonychiurus and placed in Micronychiurus Bagnall, 1949, Thalassaphorura Bagnall, 1949 and Spinonychiurus Weiner, 1996 respectively. The synonymy of Thibaudichiurus Weiner, 1996 with Allonychiurus is rejected and Allonychiurus foliatus (Rusek, 1967) and Allonychiurus mariangeae (Thibaud & Lee, 1994) are re-allocated to Thibaudichiurus. List and identification key to the world species of the genus are given.